Purification and characterization of lipoprotein lipase from pig myocardium. - Ehnholm, C (1975)
1. Lipoprotein lipase was purified from pig myocardium by a two-step purification procedure involving (a) the formation of an enzyme-substrate complex and (b) affinity chromatography on Sepharose which contained covalently linked heparin. The purified enzyme gave in sodium dodecyl sulphate-polyacrylamide-gel electrophoresis one main band with an apparent molecular weight of 73 000. The enzyme, which was purified 70 000-fold, had a specific activity of 860 mumol of unesterified fatty acid liberated/h per mg of protein. 2. The purified enzyme hydrolysed [14C]triolein emulsions in the absence of added cofactors but its activity was increased fivefold by adding normal human serum. Of the low-density lipoprotein apoproteins only apolipoprotein CII could be substituted for serum in activating the enzyme. This lipase had maximum activity at 0.05-0.15 M-NaCl. Heparin increased the activity of the purified enzyme twofold at low concentrations, but high concentrations inhibited. The triglyceride lipase of pig myocardium thus resembles lipoprotein lipase purified from adipose tissue and from plasma, but is clearly different from pig hepatic triglyceride lipase.